How personality factors, coping with identity-stress, and parental rearing styles contribute to the expression of somatic complaints in emerging adults in seven countries - Seiffge-Krenke, Inge; Sattel, Heribert (Frontiers in Psychiatry, 2024)
Objective Somatic complaints are frequently named by emerging adults in many countries, but psychological factors contributing to the high level of these often medically unexplained symptoms have received little attention. This study examines the influence of shared risk factors on somatic complaints in a culturally diverse sample. Methods and measures In a cross-cultural survey study of 2,113 emerging adults (mean age = 22.0 yrs.; SD = 2.04) from seven countries (France, Germany, Turkey, Greece, Peru, Pakistan, and Poland) personality variables, parental rearing styles, coping abilities as well as identity-related stress were assessed. In a second step we successively entered these variables in hierarchical linear mixed models, controlling for country and gender effects and their respective interaction, in order to determine their impact on the level of somatic complaints across countries. Results All these dimensions varied extensively between all countries, with females reporting higher levels of somatic complaints than men in several countries. Despite this variation, our findings demonstrate a general and stable influence of neuroticism, openness, parental rearing styles, coping abilities and identity-related stress on somatic complaints across countries. Conclusion Findings support the use of a general intervention model that includes appropriate coping strategies for emotion regulation, but also encourages support seeking for age-specific problems in dealing with identity stress during the transition to adulthood. In addition, this intervention model should be adjusted for a specific culture and gender.